Sofrimento moral e satisfação profissional:qual a sua relação na atuação do enfermeiro? - Wachholz, Aline (2017)
The accomplishment of nursing work involves the complexity of multiprofessional relations and the usual precarious working conditions offered in the institution, including lack of material and human resources. These difficulties may compromise the development and engagement of the professional regarding work and compromise the quality of care provided, which may leave these workers more susceptible to conflicts and moral dilemmas. Due to these aspects, professionals may experience moral distress at work, which, in turn, causing implications for professional satisfaction, which is understood as a subjective evaluation of the worker on how labor aspects may be harmful or beneficial to the worker’s well-being. Thus, a guiding question was presented: "What is the relation between moral distress and professional satisfaction of Nurses?" As a general objective of the research: to verify relations between moral distress and professional satisfaction in nurses' work in the hospital context. And as specific objectives: To characterize the sample according to sociodemographic and labor data; To identify the level of professional satisfaction of nurses in the hospital context; and, Identify the intensity and frequency of the moral distress of nurses in the hospital context. This is a cross-sectional study, developed at the University Hospital of Santa Maria (HUSM), located in the city of Santa Maria, RS. The participants were 141 nurses who have worked for at least three months in the service during the data collection period from January to March 2015. Two instruments were used, one to investigate professional satisfaction called the Index of Work Satisfaction (IWS), and another to investigate moral distress, called Moral Distress Scale-Brazilian Version. Descriptive statistics, factorial analysis and Spearman correlation were used for data analysis. The ethical aspects were respected, in accordance to Resolution 466/2012. The results were presented by means of scientific article entitled "Moral distress and professional satisfaction of nurses: is there a relation between these phenomena?" In which a professional satisfaction index of 10.81 was found, and that the autonomy and interaction components are among the ones that most influence satisfaction. The greatest intensity of moral suffering was the lack of competence in the team, and the greatest frequency of moral distress linked to insufficient working conditions. There were no significant correlations between the evaluation instruments. It is concluded that further studies are needed to identify this possible relation, and the development of strategies that contribute to a healthier working environment in which the occurrence of moral distress is minimized and professional satisfaction is promoted.